Older Adults with Hoarding Behaviour Aging in Place: Looking to a Collaborative Community-Based Planning Approach for Solutions. (12th October 2011) - Whitfield, Kyle Y.; Daniels, Jason S.; Flesaker, Keri; Simmons, Doneka
Abstract : This paper reports on and synthesizes new research that examines how a collaborative community response can promote successful aging in place for older adults with hoarding behaviour. Through interviews with older adults with hoarding behaviour, who used a particular community support and a focus group interview with members of the community collaborative that directed supports for this population, our findings suggest that there were valuable outcomes for both groups. These older adults with hoarding behaviour were able to remain in their own homes, their safety was enhanced, their sense of isolation was minimized, empowerment was fostered, and they gained valuable insight into their behaviour. The members of the community collaborative were able to access the expertise of other professionals, maximize their own expertise, and they generated an enhanced understanding of the experience of older adults living with hoarding behaviour in Edmonton. This study is a significant addition to the much too sparse literature about the community planning needs of older adults with hoarding behaviour. It offers knowledge that is integral to theories and principles of better aging in place but attempts to translate this into practice.